If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 66n + 16 = 14 Reorder the terms: 16 + 66n = 14 Solving 16 + 66n = 14 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 66n = 14 + -16 Combine like terms: 16 + -16 = 0 0 + 66n = 14 + -16 66n = 14 + -16 Combine like terms: 14 + -16 = -2 66n = -2 Divide each side by '66'. n = -0.0303030303 Simplifying n = -0.0303030303
| 3+t=-4 | | -17=5(2x+3)-12 | | 2x+1=7x-1 | | 27=-3u | | (16x+40)+5=8(x+8) | | 2t-3=-19 | | y=-4-19 | | 4w+6=22w | | W+19=47 | | 2a=2.8 | | 4m-2n=18 | | 7+3k=-14 | | 145x=(106)(145)+106x | | y=-4(-5)-19 | | 155x=(106)(155)+106x | | -3(n-2)+5n=2(-3n+4)-2n+1 | | 7x-3+5x+3=180 | | 4(3x-5)+6=2x-14 | | 24=-4m | | 7x-3+5x+3=90 | | 2x-6=52 | | 13=(5-8m) | | -9(4x-6)=27 | | -4(4-3m)=-52 | | 16n^2-36= | | -17=5n-20 | | -(6x+(4x+3))=7-(5x+6) | | px-qr=-r | | 3(x-1)+8=-10 | | 2*3*4x-2*3*5x=6 | | 2=4c-2 | | 6n-20+5n=2(n+4)+4n-35 |